2016
DOI: 10.15376/biores.11.1.1843-1854
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sugar Alcohol Production from Cellulose by Pretreatment with Mixed Ball-Milling and Solid Acids

Abstract: Efficient pretreatment is the key step in catalytic biomass conversion. Herein, a mixed ball-milling method was used to pretreat cellulose with a solid catalyst. The method was tested with solid acid and commercial 5 wt% Ru/C in water, and the effect of pretreatment on yield was measured by the hydrolytic-hydrogenation of cellulose to sugar alcohols, which are the platform compounds for the production of gasoline and fine chemicals. The influence of ball-milling mode, time, and reaction parameters was studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
6
0
1
Order By: Relevance
“…It is noted that the highest yield was obtained within a narrow temperature window (100-120 °C), and beyond that, the yield was decreased due to the possible side reactions (hydrogenolysis, dehydration and humin formations) of sugar alcohols, which was also observed by other researchers. 72,73 Apart from a batch reaction, a temperature effect is also noticed for the hydrogenation of sugars to sugar alcohols in the continuous flow reactor, with the Ru-carbon foam as a catalyst at 120 °C. 74 Hence, 120 °C is optimized with our catalysts for executing high xylitol (96%) and sorbitol (89%) selectivity.…”
Section: Catalytic Activity Testmentioning
confidence: 99%
“…It is noted that the highest yield was obtained within a narrow temperature window (100-120 °C), and beyond that, the yield was decreased due to the possible side reactions (hydrogenolysis, dehydration and humin formations) of sugar alcohols, which was also observed by other researchers. 72,73 Apart from a batch reaction, a temperature effect is also noticed for the hydrogenation of sugars to sugar alcohols in the continuous flow reactor, with the Ru-carbon foam as a catalyst at 120 °C. 74 Hence, 120 °C is optimized with our catalysts for executing high xylitol (96%) and sorbitol (89%) selectivity.…”
Section: Catalytic Activity Testmentioning
confidence: 99%
“…Evidently, a desirable ML yield was obtained from ball-milled cellulose in a reasonable time at a mild temperature. This notable enhancement is attributed to the reduction of the cellulose particle http://engine.scichina.com/doi/10.1016/j.jechem.2017.11.005 size inducing the cleavage of the glycosidic linkage [37] and the deconstruction of crystalline cellulose into amorphous as well as the surface degradation of cellulose due to carbonization and/or oxidization [36] . Previous research showed the fibrillar structure and crystallinity of the cellulosic samples could have a significant impact on mass transportation [14,38] , thus ball milling can be an efficient processing method for mass transportation of cellulose.…”
Section: Influence Of the Ball-milling Pretreatment On Cellulose Alcomentioning
confidence: 99%
“…Independently of the support, Ni in bimetallic nanoparticles had a promoting effect on catalysis, increasing conversion, and selectivity to sorbitol due to intimate interaction of both metals. The sorbitol yield was in the range of 50–60% (205°C, 5 MPa, 5 h), but it could be further increased to more than 70% when cellulose and catalysts were milled together, an important development in the catalyst pretreatment (Ribeiro et al, 2015a; Liu et al, 2016b). These catalysts preserved their activity in at least four consecutive reactions.…”
Section: Cellulose Hydrolytic Hydrogenationmentioning
confidence: 99%